Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies